Structural and functional consequences of the STAT5BN642H driver mutation - Elvin D. de Araujo (Nature Portfolio, 2019)
Hyper-activated STAT5B and its disease-causing variants are of interest as cancer drug targets. Here the authors combine cell based studies, X-ray crystallography, biophysical experiments and MD simulations to structurally and functionally characterize the STAT5BN642H mutant found in aggressive T-cell leukemia and lymphomas and find that it has an increased affinity for self-dimerization.